LB14. Safety and Immunogenicity of High-Dose Quadrivalent Influenza Vaccine Administered by Intramuscular Route in Subjects Aged 65 Years and Older. (26th November 2018) - Chang, Lee-Jah; Meng, Ya; Janosczyk, Helene; Landolfi, Victoria; Talbot, H Keipp; ,
Abstract: Background: Older adults (≥65 years of age) remain at increased risk of influenza because they do not respond to standard dose influenza vaccines as well as younger adults. A high dose, inactivated trivalent influenza vaccine, IIV3-HD, containing four times the antigen content (60 µg hemagglutinin per influenza strain) of standard-dose influenza vaccines has been available in the United States since 2010. Two distinct B influenza lineages (Victoria and Yamagata) have co-circulated for over a decade, making it difficult to predict which will predominate the next season. IIV4-HD has been developed to address the frequent influenza B strain mismatches by incorporating a strain from each B lineage. This pivotal Phase III study evaluated the safety and immunogenicity of IIV4-HD as compared with two IIV3-HD vaccines. Method: A randomized, modified double-blind, multicenter study (NCT03282240) was conducted in 2670 healthy subjects in the United States, who were randomly assigned to receive IIV4-HD, a licensed IIV3-HD, or an IIV3-HD with the alternate B influenza strain. Using the hemagglutinin inhibition (HAI) assay at baseline and 28 days after vaccination, post-vaccination geometric mean titers and seroconversion rates were measured. Safety data were collected through 6 months post-vaccination. Result: IIV4-HD was noninferior to the licensed IIV3-HD and the investigational IIV3-HD (containing the alternate B strain) for all four influenza strains as assessed by HAI GMTs and seroconversion rates. Moreover, IIV4-HD induced a superior immune response (HAI GMTs and seroconversion rates) compared with the immune response induced by the IIV3-HD that does not contain the corresponding B strain. Reactogenicity profiles were comparable across all study groups. Most unsolicited adverse events were of Grade 1 or Grade 2 intensity. One serious adverse event considered related by the Investigator was reported in the IIV4-HD group. Conclusion: Vaccination of adults 65 years of age and older with IIV4-HD was found to be noninferior to two IIV3-HD vaccines with a similar safety profile. The addition of a second B lineage strain does not adversely affect the safety or immunogenicity profile of IIV4-HD compared with IIV3-HD. Disclosures: L. J. Chang, Sanofi Pasteur: Employee, Salary. Y. Meng, Sanofi Pasteur: Employee, Salary. H. Janosczyk, Sanofi Pasteur: Employee, Salary. V. Landolfi, Sanofi Pasteur: Employee, Salary. H. K. Talbot, Sanofi Pasteur: Investigator, Research grant. Gilead: Investigator, Research grant. MedImmune: Investigator, Research grant. Vaxinnate: Safety Board, none. Seqirus: Safety Board, none.